2000
DOI: 10.1021/bp000118j
|View full text |Cite
|
Sign up to set email alerts
|

Two-Liquid-Phase Slurry Bioreactors To Enhance the Degradation of High-Molecular-Weight Polycyclic Aromatic Hydrocarbons in Soil

Abstract: High-molecular-weight (HMW) polycyclic aromatic hydrocarbons (PAHs) are pollutants that persist in the environment due to their low solubility in water and their sequestration by soil and sediments. The addition of a water-immiscible, nonbiodegradable, and biocompatible liquid, silicone oil, to a soil slurry was studied to promote the desorption of PAHs from soil and to increase their bioavailability. First, the transfer into silicone oil of phenanthrene, pyrene, chrysene, and benzo[a]pyrene added to a sterili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 40 publications
1
39
0
Order By: Relevance
“…A log P value for silicone oil was not found but silicone oil has been successfully demonstrated as an immiscible liquid for a number of twophase applications. Guieysse et al (2001); Villemur et al (2000). Figure 1.…”
Section: Selection Of An Appropriate Immiscible Liquidmentioning
confidence: 99%
See 1 more Smart Citation
“…A log P value for silicone oil was not found but silicone oil has been successfully demonstrated as an immiscible liquid for a number of twophase applications. Guieysse et al (2001); Villemur et al (2000). Figure 1.…”
Section: Selection Of An Appropriate Immiscible Liquidmentioning
confidence: 99%
“…was selected as it has been shown to be an effective immiscible liquid in two-phase systems (Tikhomiroff et al, 2002;Villemur et al, 2000) demonstrating both biocompatibility and non-bioavailability.…”
Section: Selection Of An Appropriate Immiscible Liquidmentioning
confidence: 99%
“…This selfimposed metabolic limitation of using pure cultures is somewhat off-set by the fact that, through rational solvent selection (Bruce & Daugulis 1991), an organic delivery phase can be tailored to a substrate/organism pairing, usually with excellent performance. A few studies (Guieysse et al 2001a;Marcoux et al 2000;Villemur et al 2000) have employed silicone oil as a delivery phase, due exclusively to its non-biodegradability, along with mixed cultures, however, the properties of silicone oil are, for better or for worse fixed; silicone oil thus provides no opportunity for enhancing important solvent properties such as substrate solubility, substrate distribution coefficient, viscosity, etc. as different substrates are selected.…”
Section: Introductionmentioning
confidence: 99%
“…Cost increases in the case of post-gas treatment requirements for volatile contaminants (US EPA 2012 ). Villemur et al ( 2000 ) used a three-phase, aerobic slurry system containing 30 % silicone oil and biodegraded 90-98 % chrysene, pyrene and BaP. Wang and Vipulanandar ( 2001 ) observed that 96-99 % naphthalene was rapidly degraded by aerobic slurry bioreactors in 4 days.…”
Section: Slurry-phase Bioremediation: Bioreactorsmentioning
confidence: 99%